A qualitative study of the barriers to commissioning social and therapeutic horticulture in mental health care - Carly J. Wood; Georgina Morton; Kathryn Rossiter; Becs Baumber; Rachel E. Bragg (BMC, 2024)
Abstract Background Social and Therapeutic Horticulture (STH) is a process where trained practitioners work with plants and people to improve an individual's physical and psychological health, communication and thinking skills. Evidence suggests that STH can support individuals with mental ill-health, however, current commissioning of STH within mental health care is limited. This study aimed to understand the barriers to commissioning STH in mental health care and to identify potential solutions to barriers, to support more widespread availability of services.  Methods Individuals with a role in mental health care commissioning from across the UK were invited to take part in semi-structured interviews via zoom. Interviews explored factors influencing the mental health services they commission or refer to, their perception of the role of STH in mental health care and the barriers to commissioning STH, together with potential solutions to any barriers identified. Results Commissioners identified a lack of knowledge of STH and evidence of its effectiveness, and a culture which prioritises traditional medical models, as barriers to commissioning. Challenges for STH providers in responding to large-scale commissioning requirements were also highlighted as a barrier. Conclusions To upscale commissioning of STH in mental health care, STH interventions need to be embedded within NHS priorities and information on STH services and their effectiveness needs to be easily accessible to practitioners. The sector should also be supported in working collaboratively to enable commissioning of services at scale.